Agronomic Performance and Nutrition Content of Hiyung as Local Variety of Cayenne Pepper [Capsicum frutescens] at Dry Land and Swamp Land of South Kalimantan Province - Lelya Pramudyani; M. Sabran; Aidi Noor (Buletin Plasma Nutfah, 2019)
Hiyung is a local variety of cayenne pepper (Capsicum frutescens) that traditionally grown continuously at swampland of Tapin District, South Kalimantan Province. This cayenne pepper has high productivity and good market prospect and could contribute to increase national cayenne production. Another advantage of this cayenne pepper variety is enabling farmers to use some of the harvested seeds for the next planting season. The experiment has been conducted to characterize the agronomics and nutrition contents of Hiyung cayenne pepper from March to October 2013 at two different agroecosystems, i.e. dry land and swampland, and to compare it with three commercial varieties, i.e. Sonar, Bara, and Santika. The result of the experiment showed that Hiyung cayenne pepper, both at dry land and swampland, has the highest dry weight than the three other varieties. It also had the lowest fruit length, peel thickness, fruit weight, and weight of 1,000 fruits compare to the three other varieties. However, it had the highest productivity, which might be due to its longest harvest period.